Comparative Historiography Teaching: the Problem of Research Methodology - Yuriі Chopyk (Pedagogical Discourse, 2016)
The problem of developing a methodological research program teaching comparative historiography we should see in the artice. In the context of scientific discourse, based on the works of Ukrainian and foreign scientists, investigated the theoretical and methodological aspects of defining the subject, objectives, and other components of Comparative Education and historiography of science teaching. We consider the scientific tools of scientific studies in the defined area. The model analysis of research on comparative pedagogy includes: determining the nature of the information to solve the problem and to confirm or refute the hypothesis of the study: the search for optimal approaches to the selection of the most efficient sources and information; exercise their critical and constructive analysis and comprehensive reconsideration; clarify the potential strengths or weaknesses of the chosen structure research. Optimal approaches to the use of such methods of research: methods of scientific description information; Chief array methods and sample analysis; comparative teaching methods of analysis and discus cross-analysis.Key words: comparative teacher, historiography pedagogy, methodology of scientific research.